Antimicrobial Activity of Sponges Endemic to Uchipully Coastal Line Near Rameswaram Tamilnadu - Ernest David, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Antimicrobial Activity of Sponges Endemic to Uchipully Coastal Line Near Rameswaram Tamilnadu